Gambaran kadar hemoglobin pasien pra dan pasca operasi seksio sesarea yang tidak mendapat transfusi darah - Tia, Herry Y.; Kumaat, Lucky T.; Lalenoh, Diana Ch. (Universitas Sam Ratulangi, 2016)
Abstract: The occurence of increased or decreased levels of hemoglobin of post-caesarean patients depends on the intake of nutrients during pregnancy, bleeding, and anemia. In case of massive and life-threatening bleeding during the caesarean section, blood transfusion has to be administered to revive the patient in critical condition. This study was aimed to obtain the patientsâ€™ levels of hemoglobin in either pre- and post-operative caesarean section without blood transfusion. This was a retrospective descriptive study using data of medical records at the Installation of Medical Record Department of Prof. Dr. R. D. Kandou Hospital Manado from September 2015 to August 2016. There were 32 patients in this study. The result showed that the mean values of pre-operative Hb was 12.4 g/dL and of post-operative Hb was 11.5 g/dL with a difference of 0.9 g/dL. Decreased levels of hemoglobin occured in 28 patients. It is discerned that the mean value of pre-operative Hb was 12.4 g/dL while of post-operative Hb was 11.3 g/dL with a difference of 1.1 g/dL. Furthermore, increased levels of hemoglobin occured in 4 patients, showing that the mean value of pre-operative Hb was 12.1 g/dLwhereas of post-operative Hb was 12.5 g/dL with a difference of 0.4 g/dL. Based on the characteristics of pregnant women, 23 cases (71.9%), were in the age group of 20-35 years; 18 cases (56.3%) of hemorrhage of 500-1000 ml; and 25 cases (78.1%) of 6-10 days length of hospitalization. Conclusion: In this study, there was increased as well as decreased hemoglobin levels in caesarean patients who were not administered blood transfusion during surgery.Keywords: hemoglobin, caesarean section, blood transfusionÂ Abstrak: Terjadinya peningkatan maupun penurunan kadar hemoglobin pada operasi seksio sesarea tergantung pada asupan zat-zat nutrisi saat kehamilan, perdarahan, dan anemia. Jika terjadi perdarahan hebat selama operasi seksio sesarea berlangsung yang mengakibatkan penurunan kadar hemoglobin mendekati batasan untuk dilakukan transfusi darah, maka transfusi darah diberikan untuk menolong pasien pada kondisi kritis. Penelitian ini bertujuan untuk mengetahui gambaran kadar hemoglobin pasien pra dan pasca operasi seksio sesarea yang tidak mendapat transfusi darah. Jenis penelitian ialah deskriptif retrospektif menggunakan data rekam medik pasien seksio sesarea di Instalasi Rekam Medik RSUP Prof. Dr. R. D. Kandou Manado periode September 2015 sampai Agustus 2016. Hasil penelitian memperlihatkan 32 pasien yang memenuhi kriteria inklusi. Nilai mean kadar Hb pra 12,4 g/dL dan kadar Hb pasca 11,5 g/dL dengan selisih 0,9 g/dL. Penurunan kadar hemoglobin terdapat pada 28 pasien dengan nilai mean kadar Hb pra 12,4 g/dL dan kadar Hb pasca 11,3 g/dL (selisih 1,1 g/dL). Peningkatan kadar hemoglobin terdapat pada 4 pasien dengan nilai mean kadar Hb pra 12,1 g/dL dan kadar Hb pasca 12,5 g/dL (selisih 0,4 g/dL). Karakteristik ibu hamil didapatkan terbanyak kelompok usia 20-35 tahun berjumlah 23 kasus (71,9%), perdarahan 500-1000 cc berjumlah 18 kasus (56,3%), dan lama rawat inap 6-10 hari berjumlah 25 kasus (78,1%). Simpulan: Pada pasien operasi seksio sesarea yang tidak mendapat transfusi darah dapat terjadi penurunan maupun peningkatan kadar hemoglobin. Kata kunci: hemoglobin, seksio sesarea, transfusi darah